MEDIA TRANSMISSION IN LOCAL AREA NETWORK DI PT. TELKOM KANDATEL EAST JAKARTA - Ruddy Bakhtiar; Jalinas Jalinas Skom., MMSI (Jurnal Sistem Komputer, 1996)
LAN network in the East Jakarta Kandatel to send its data he uses communication techniques broandband ethernet, using CSMA / CD (Carrier Sense Multiple Access / Collision Detection with) and the topology used is the bus topology used in the building. While the tree topology t o connect between buildings OPMC, Datel and Sentel through optical fiber media. While for the LAN network in a single building using UTP cable. In Kandatel to connect between buildings with each other using fiber optic media, it is because this type of cab le is not easily disrupted by interference from outside. While for the LAN network in a building using UTP cable.Â